Ultrastructural Analysis of In Vivo Hypoglycemiant Effect of Two Polyoxometalates in Rats with Streptozotocin-Induced Diabetes. (7th September 2015) - Bâlici, Ştefana; Wankeu-Nya, Modeste; Rusu, Dan; Nicula, Gheorghe Z.; Rusu, Mariana; Florea, Adrian; Matei, Horea
Abstract: Two polyoxometalates (POMs), synthesized through a self-assembling method, were used in the treatment of streptozotocin (STZ)-induced diabetic rats. One of these nanocompounds [tris(vanadyl)-substituted tungsto-antimonate(III)-anions—POM1] was previously described in the literature, whereas the second [tris-butyltin-21-tungsto-9-antimonate(III)-anions—POM2], was prepared by us based on our original formula. In rats with STZ-induced diabetes treated with POMs (up to a cumulative dose of 4 mg/kg bodyweight at the end of the treatments), statistically significant reduced levels of blood glucose were measured after 3 weeks, as compared with the diabetic control groups (DCGs). Ultrastructural analysis of pancreatic β -cells (including the mean diameter of secretory vesicles and of their insulin granules) in the treated diabetic rats proved the POMs contribute to limitation of cellular degeneration triggered by STZ, as well as to the presence of increased amounts of insulin-containing vesicles as compared with the DCG. The two POMs also showed hepatoprotective properties when ultrastructural aspects of hepatocytes in the experimental groups of rats were studied. Based on our in vivo studies, we concluded that the two POMs tested achieved hypoglycemiant effects by preventing STZ-triggered apoptosis of pancreatic β -cells and stimulation of insulin synthesis.